2022
DOI: 10.32634/0869-8155-2022-361-7-8-98-101
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of probiotics in industrial pig breeding

Abstract: Pig breeding is one of the leading agricultural sectors that ensures the country’s food safety. In this regard, pig breeding must become a highly profitable branch of the agro-industrial complex due to growth of range of production performance indicators. Various feed additives are the reserve for increasing the productivity of the animals. The most popular feed supplements used today are probiotics and phytobiotics. Modern probiotic preparations are a complex (symbiotic additives) consisting of various strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It was also revealed that the use of probiotics and synbiotics to sows affects the gastrointestinal microbiota of the pig itself and their offspring, as well as health and productivity, according to an analysis conducted in the study by Kiernan D.P. et al [5].…”
Section: Resultsmentioning
confidence: 99%
“…It was also revealed that the use of probiotics and synbiotics to sows affects the gastrointestinal microbiota of the pig itself and their offspring, as well as health and productivity, according to an analysis conducted in the study by Kiernan D.P. et al [5].…”
Section: Resultsmentioning
confidence: 99%
“…The feed additive contributed to an increase in the antioxidant activity of the animal organism and the antimicrobial components of blood plasma [17]. Probiotics and phytobiotics show their efficiency too [18,19]. Thus, the application of yeast probiotic supplements positively affects the content of erythrocytes, total protein, calcium and phosphorus in the blood of animals, as well as the number of lactobacteria and bifidobacteria in the intestine, increases live weight and increases rate of multiple pregnancy [20,21].…”
Section: Introductionmentioning
confidence: 99%